Transfusional Approach in Multi-Ethnic Sickle Cell Patients: Real-World Practice Data From a Multicenter Survey in Italy - Graziadei, Giovanna; De Franceschi, Lucia; Sainati, Laura; Venturelli, Donatella; Masera, Nicoletta; Bonomo, Piero; Vassanelli, Aurora; Casale, Maddalena; Lodi, Gianluca; Voi, Vincenzo; Rigano, Paolo; Pinto, Valeria Maria; et al. (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) is a worldwide distributed hereditary red cell disorder characterized by recurrent acute vaso-occlusive crises (VOCs and anemia). Gold standard treatments are hydroxycarbamide (HC) and/or different red blood cell (RBC) transfusion regimens to limit disease progression. Here, we report a retrospective study on 1,579 SCD patients (median age 23 years; 802 males/777 females), referring to 34 comprehensive Italian centers for hemoglobinopathies. Although we observed a similar proportion of Caucasian (47.9%) and African (48.7%) patients, Italian SCD patients clustered into two distinct overall groups: children of African descent and adults of Caucasian descent. We found a subset of SCD patients requiring more intensive therapy with a combination of HC plus chronic transfusion regimen, due to partial failure of HC treatment alone in preventing or reducing sickle cell-related acute manifestations. Notably, we observed a higher use of acute transfusion approaches for SCD patients of African descent when compared to Caucasian subjects. This might be related to (i) age of starting HC treatment; (ii) patients' low social status; (iii) patients' limited access to family practitioners; or (iv) discrimination. In our cohort, alloimmunization was documented in 135 patients (8.5%) and was more common in Caucasians (10.3%) than in Africans (6.6%). Alloimmunization was similar in male and female and more frequent in adults than in children. Our study reinforces the importance of donor-recipient exact matching for ABO, Rhesus, and Kell antigen systems for RBC compatibility as a winning strategy to avoid or limit alloimmunization events that negatively impact the clinical management of SCD-related severe complications. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT03397017.